Menghilang Tanpa Jejak: Pemutusan Hubungan Satu Pihak Dalam Suatu Hubungan - Cyndy, Cyndy; Muh Nur Hidayat Nurdin; Tri Sulastri (CV. Ulil Albab Corp, 2025)
The phenomenon of unilateral relationship termination occurs when one party ends a romantic relationship without prior discussion or agreement with their partner. This study explores the dynamics behind unilateral relationship termination from the perspective of the initiator. Using a qualitative phenomenological approach, data were collected through in-depth interviews with four respondents aged 20–23 who had experienced ending a romantic relationship unilaterally. The results reveal that respondents used avoidance strategies, such as gradually reducing communication, blocking social media, and disappearing without explanation. Factors influencing this decision include external pressures (family, work, and friends) and internal reasons (boredom, dissatisfaction, and emotional stress). Although some respondents felt relieved after ending the relationship, others experienced guilt and reflection on their actions. This study highlights the emotional complexity involved in unilateral breakups and emphasizes the importance of open communication to avoid unresolved emotional consequences. Future research should explore the long-term impact of this phenomenon on individuals' future romantic relationships.